Cancer Care Management During the COVID-19 Pandemic - Jafari A; Rezaei-Tavirani M; Karami S; Yazdani M; Zali H; Jafari Z (Dove Medical Press, 2020)
Ameneh Jafari,1,2 Mostafa Rezaei-Tavirani,1 Samira Karami,3 Mohsen Yazdani,4 Hakimeh Zali,1,5 Zahra Jafari6 1Proteomics Research Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Student Research Committee, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Hematopoietic Stem Cell Research Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 4Department of Bioinformatics, Institute of Biochemistry and Biophysics, University of Tehran, Tehran, Iran; 5Department of Tissue Engineering and Applied Cell Sciences, School of Advanced Technologies in Medicine, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 6 9Dey Manzariye Hospital, Isfahan University of Medical Sciences, Isfahan, IranCorrespondence: Hakimeh Zali Department of Tissue Engineering and Applied Sciences, School of Advanced Technologies in MedicineShahid Beheshti University of Medical Sciences, Tehran, IranTel +989123367156Fax +982122439848Email hakimehzali@gmail.comMostafa Rezaei-TaviraniProteomics Research Center, School of Allied Medical SciencesShahid Beheshti University of Medical Sciences, Tehran, IranTel +982122439787Email tavirany@yahoo.comAbstract: New cases of the novel coronavirus, also known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), are increasing around the world. Currently, health care services are mainly focused on responding to and controlling the unique challenges of the coronavirus disease 2019 (COVID-19) pandemic. These changes, along with the higher susceptibility of patients with cancer to infections, have profound effects on other critical aspects of care and pose a serious challenge for the treatment of such patients. During the COVID-19 pandemic, it is important to provide strategies for managing the treatment of patients with cancer to limit COVID-19-associated risks at this difficult time. The present study set out to summarize the latest research on epidemiology, pathogenesis, and clinical features of COVID-19. We also address some of the current challenges associated with the management of patients with cancer during the COVID-19 pandemic and provide practical guidance to clinically deal with these challenges.Keywords: coronavirus, SARS-CoV-2, cancer, pandemic, health care